Evaluation of Risk Management practices and their relationship to the Entrepreneur behavior of managers in insurance companies: applied research (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The objective of the research is to evaluate the risk management practices of the variables (risk management structure, risk management methods, key components of risk management) and their relation to the principled behavior of managers behavior(innovation, proactive, risk acceptance) By adopting the questionnaire as a main tool in collecting data from managers in the National and raq insurance companies of (50) officials Department manager, department administrator, unit administrator, and analyzed their answers using the SPSS In calculating arithmetic mean, standard deviation, percentage weight and simple correlation coefficient. The most prominent conclusions were:1.There is a positive trend in the sample in both companies and a high degree of risk management practice.  2.There is a positive and strong relationship between risk management and leadership behavior in both companies.